Selective Laser Trabeculoplasty as First-Line Treatment in Primary Open Angle Glaucoma: A Meta-Analysis - Rifa'i, Alfiani Zukhruful Fitri; Hartono, Faigah Diva; Fazarrahmah (Oftalmologi : Jurnal Kesehatan Mata Indonesia, 2025)
Introduction: For primary open-angle glaucoma (POAG), selective laser trabeculoplasty (SLT) is a non-invasive therapeutic approach that provides an alternative to conventional operations and medications. The effectiveness and safety profile of SLT as a primary treatment for newly diagnosed POAG were evaluated by a meta-analysis. Methods: A systematic review and meta-analysis were performed using databases including PubMed, ScienceDirect, ProQuest, and Scopus from inception to March 2025, adhering to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Analyses were executed via Review Manager 5.4.1. Subgroup analyses were performed on SLT compared with medical therapy and categorized SLT as initial or adjunctive therapy. Results: Out of twelve qualifying trials, 2.248 patients were combined. In newly diagnosed POAG, the results showed no significant differences in IOP reduction between SLT and topical medications as first line modality (Mean Difference (MD): 0.21, 95% CI 0.81 to 1.83, p=0.69, I2 = 70%); however, initial SLT performed better than adjunctive SLT (MD: 0.57, p=0.05, I2: 37%). Antiglaucoma drug use, glaucoma surgery rates, and ocular side effects were all markedly lower in the SLT group. Conclusion: SLT has the potential to transform glaucoma management due to its enhanced efficacy, minimal adverse effects, reduced medication burden, and cost-effectiveness.